Development of a Green School-Based Madrasah Tsanawiyah Management Model in Pesawaran District - Hapid, Hapid; Pahrudin, Agus; Syafril, Syafrimen; Koderi, Koderi; Patimah, Siti (International Journal of Financial, Accounting, and Management, 2024)
Purpose: The development of a green school-based madrasah management model can have a positive impact on social and economic aspects. This is because the implementation of green school requires more efficient use of technology and resources, thus reducing operational costs and increasing productivity. This research explores the development of a management model for Green School-based Madrasahs in Pesawaran District as a strategy to improve the quality of education and environmental awareness. Method: The method used in this research is descriptive qualitative method. Data sources in this study include primary data and secondary data. Data collection techniques through observation, interviews and documentation. Data analysis, through data (data collection), data reduction (data reduction), data presentation (data display) and conclusion (conclusion) or verification (verification). Data validity check through tringulation. Result: The stages of planning, organizing, implementing, and monitoring are described with a focus on stakeholder participation, the establishment of an organizational structure, the implementation of an environment-based curriculum, and awareness-raising efforts. Despite showing positive progress, obstacles such as limited resources, lack of awareness, absence of supporting policies, community response, and limited access to green technologies pose challenges. Careful oversight involving monitoring, performance evaluation, feedback and continuous improvement is needed to maintain the sustainability of Green School. Contribution: This research provides a foundation for the development of a sustainable Green School-based management model in Madrasah Tsanawiyah Pesawaran District.